Influence of Cellular Composition and Exogenous Activation on Growth Factor and Cytokine Concentrations in Canine Platelet-Rich Plasmas - Franklin, Samuel P.; Birdwhistell, Kate E.; Strelchik, Alena; Garner, Bridget C.; Brainard, Benjamin M. (Frontiers in Veterinary Science, 2017)
Objective: The purposes of this study were to 1) evaluate correlations among platelet, leukocyte, growth factor, and cytokine concentrations in canine platelet-rich plasmas (PRPs) produced from five different canine PRP concentrating systems and 2) compare the effects of different activation protocols on platelet activation and growth factor release from one of these PRPs. Methods: PRP was made using blood from 15 dogs and each of 5 different PRP systems in a cross-over design. Complete blood counts were performed to quantify platelet and leukocyte concentrations. PRPs were activated, or not, according to manufacturer instructions and transforming growth factor-β1 (TGF- β1), platelet-derived growth factor-BB (PDGF-BB), vascular endothelial growth factor (VEGF), and tumor necrosis factor- alpha (TNF-α) were quantified. Differences among platelet, leukocyte, and growth factor concentration were compared among the different systems. Correlations between platelet and anabolic growth factor concentrations were assessed. Subsequently, PRP was made from 12 additional dogs using one of the devices. Each PRP was divided into three aliquots that were activated with calcium chloride (CaCl2), human γ-thrombin (HGT), or not activated. Expression of CD62P and platelet-bound fibrinogen (CAP1) was quantified for each activation group. Concentrations TGF-β1, PDGF-BB, and TNF-α were also quantified for each activation group and a fourth group that was frozen/thawed. Differences among activation groups were assessed by a Friedman test. Results: There were statistically significant differences among the PRPs made with difference devices with regards to platelet, leukocyte, TGF-β1, and PDGF-BB concentrations (p<0.0001). There were weak to moderate correlations (R2 = 0.07 – 0.58) between platelet and anabolic growth factor concentrations but it appeared that activation had a greater effect on growth factor concentration than did cellular composition. Intentional platelet activation significantly increased CD62P and CAP1 expression as well as TGF-β1 and PDGF-BB concentrations in the one PRP in which all activation methods were assessed. Activation with HGT resulted in the greatest platelet activation and CaCl2 and freeze/thaw elicited moderate increases in either growth factor release or CD62P and CAP1 expression. Conclusions: There are positive correlations between platelet and anabolic growth factor concentrations in canine PRPs. However, intentional platelet activation has a greater effect on